Challenge-Based Learning in Aerospace Engineering Education: The ESA Concurrent Engineering Challenge at the Technical University of Madrid. (June 2020) - López-Fernández, D.; Salgado Sánchez, P.; Fernández, J.; Tinao, I.; Lapuerta, V.
Abstract: This paper analyzes from several perspectives the impact of an educational experience that combines Challenge-Based Learning, as an active learning methodology, and Concurrent Engineering, as a design methodology. This empirical research focuses on motivational aspects, professor-student relationship and the complete teaching-learning process in the scope of tertiary learning, particularly, in Aerospace Engineering Education. The experience consisted in the participation of Master students from the Universidad Politécnica de Madrid in the 2018 ESA Concurrent Engineering Challenge, which proposed the preliminary sizing of a space mission following the Concurrent Engineering approach. The positive results of the experience, obtained from different instruments and surveys presented to both students and professors, have shown enhanced student motivation and improvements in the teacher-student relationship and the overall learning process. Highlights: Educational experience combining Challenge-Based Learning & Concurrent Engineering. Empirical study based on instruments and surveys presented to students and teachers. Positive impact in the students' motivation and teacher-student relationship. Overall improvement of the learning processes in Aerospace Engineering Education.